Analysis of Production Influences on the Transmission Efficiency of Wireless Power Transfer Systems - Kneidl, Maximilian; Fuß, Tobias; Weigelt, Michael; Masuch, Michael; Kühl, Alexander; Franke, Jörg (2023 IEEE Wireless Power Technology Conference and Expo, WPTCE 2023 - Proceedings, 2023)
Wireless power transfer (WPT) systems for electric vehicles are a more customer-friendly and convenient way of charging. Moreover, it seems to be a promising solution to increase the range of electric vehicles without having to use larger batteries. In addition to the positioning of the transmitter and receiver coils, the fabrication of the individual coils can also have a crucial impact on the overall efficiency of the transmission. The main objective of this paper is to use simulation results and practical validation to determine which manufacturing processes in the automated production of inductive power transmission systems affect both system efficiency and transmission performance for inductive charging applications. From the analysis of the process steps, the resulting manufacturing deviations are determined and evaluated. First, the manufacturing influences under real conditions are determined by performance measurements. The results obtained can be used to perform a simulative loss analysis of the components. It thus provides knowledge that can be used to design and monitor each process step. Keywords - Wireless Power Transfer, Manufacturing, Simulation, Efficiency)
CRIS-Team Scopus Importer:2023-09-22

Analysis of the Rotary Cutting Process of Electrical Steel on Basis of a Toroidal Core Test - Hubert, Markus; Ziegler, Marco; Kutter, Simon; Schneider, Michael; Weigelt, Michael; Franke, Jörg; Hackert, Juergen; Mehlhorn, Marcus (2016 6th International Electric Drives Production Conference (E/DPC), 2016)
Rotary cutting of electrical steel strip is an innovative, but largely unexplored process. By state of the art a derivation of achievable process and product quality is not sufficiently possible yet. Within this publication, a series of experiments to rotary cut toroidal core specimens will be presented. With toroidal core tests on one the hand, the rotary cutting process itself is analyzed and on the other hand the results of the sample analysis reveal the process influences. Finally, a classification of the rotary cutting process into existing processing technologies of electrical steel strip is feasible with respect to its limits and possibilities.

Application Scenarios of Artificial Intelligence in Electric Drives Production - Mayr, Andreas; Weigelt, Michael; Masuch, Michael; Meiners, Moritz; Hüttel, Franziska; Franke, Jörg (Procedia Manufacturing, Volume 24, 2018)
Artificial intelligence (AI) is the overall term for technologies used to build intelligent systems, no matter whether utilized in an industrial or private environment. However, hardly any AI-based approaches have been proposed for the increasingly important electric drives production yet. By identifying and presenting exemplary application scenarios for knowledge-based systems (KBS) and machine learning (ML), the paper serves as a starting point for further research in the respective fields. Among others, the systematic overview reveals that KBS are especially suited for supporting the planning of electric drives production systems, whereas ML-based approaches have great potential for optimizing single production processes.<br
Keywords: artificial intelligenceknowledge-based systemmachine learningintelligent systemselectric drives production

A System for Wireless Inductive Power Supply of Electric Vehicles while Driving Along the Route - Russer, Johannes A.; Haider, Michael; Weigelt, Michael; Becherer, Markus; Kahlert, Sebastian; Merz, Christoph; Schindler, Markus; Franke, Jörg; Russer, Peter (2017 7th International Electric Drives Production Conference (E|DPC), 2017)
A Moving Field Inductive Power Transfer (MFIPT) system concept for wireless inductive power supply in EjROAD traffic is described. In this system, inductive power receivers are arranged along routes of inductive power stations and in the vehicles. The MFIPT system provides the contactless energy transfer from an electrified road to the electrically driven vehicles during driving by dynamic inductive charging. In order to achieve a high efficiency, only the energy channels are activated for which the radiated energy can be received by energy recipient

Automated and Flexible Production of Inductive Charging Systems as an Enabler for the Breakthrough of Electric Mobility - Weigelt, Michael; Masuch, Michael; Mayr, Andreas; Seefried, Johannes; Kühl, Alexander; Franke, Jörg (Advances in Production Research, 2018)

Challenges of Contacting Processes for Thin Copper Flat Wires in the Context of Electromechanical Engineering - Seefried, Johannes; Mahr, Alexander; Weigelt, Michael; Kühl, Alexander; Franke, Jörg (2021 11TH INTERNATIONAL ELECTRIC DRIVES PRODUCTION CONFERENCE (EDPC), 2021)
CRIS-Team WoS Importer:2022-04-29

Challenges of the Hairpin Technology for Production Techniques - Riedel, Andreas; Masuch, Michael; Weigelt, Michael; Gläßel, Tobias; Kühl, Alexander; Reinstein, Sebastian; Franke, Jörg (2018 21st International Conference on Electrical Machines and Systems (ICEMS), 2018)
The electrification of the drive train of passenger cars is currently undergoing an evolution from windings previously drawn in, which are known from industrially used electrical machines, to windings specially tailored to the requirements of mobile electric traction. A main trend is the use of pluggable shape windings, so-called hairpins. In order to fully exploit the economic advantages of this winding, elaborated production concepts and strategies are required. Due to the novelty and the currently ongoing innovation of these type of windings, the differentiated manufacturing possibilities per process step have not yet been fully defined. In view of the economic efficiency, high process speeds with increasing process reliability play a major role. The aim of this paper is to show a process chain of hairpin technology that is as universally valid as possible, to name the different alternatives for each process step and to explain their characteristic
Keywords: Wires; Windings; Insulation; Manufacturing automation; Production systems; Conductors; Hairpin; Process Chain; Production Technologies

Comparison of Additive Balancing Processes for Rotors in the Context of High Speed Electric Traction Motors - Masuch, Michael; von Lindenfels, Johannes; Seefried, Johannes; Mayr, Andreas; Schneider, Michael; Weigelt, Michael; Kühl, Alexander; Franke, Jörg; Hemmer, Christian (2019 9th International Electric Drives Production Conference (EDPC), 2019)
In the ongoing development of electric traction motors with increasing volumetric power density, concepts are being developed for rotational speeds of more than 30,000 rpm. These motors require an especially high balancing quality. Due to the unavoidable material and production fluctuations, a tuning of the mass distribution regarding the rotation axis is necessary. This balancing can be achieved by subtractive or additive process alternatives. In this paper, an overview of current balancing approaches is given first. Based on this, the potentials and challenges of additive balancing methods, which directly apply material to the lamination stack, are explained. In this context, two joining processes, namely ultrasonic welding and laser beam welding, are examined in more detail on the basis of practical experiments. In particular, influences on the quality of the lamination stack are considered.<br
Keywords: balancing; rotor; electric motor production; manufacturing; NVH; laser beam welding; ultrasonic welding

Conceptual design of an intelligent ultrasonic crimping process using machine learning algorithms - Weigelt, Michael; Mayr, Andreas; Seefried, Johannes; Heisler, Paul; Franke, Jörg (28th International Conference on Flexible Automation and Intelligent Manufacturing (FAIM2018), 2018)

Digital Twin of the Linear Winding Process Based on Explicit Finite Element Method - Weigelt, Michael; Kink, Julian; Mayr, Andreas; von Lindenfels, Johannes; Kühl, Alexander; Franke, Jörg (2019 9th International Electric Drives Production Conference (EDPC), 2019)

Electric Motor Production 4.0 – Application Potentials of Industry 4.0 Technologies in the Manufacturing of Electric Motors - Mayr, Andreas; Weigelt, Michael; von Lindenfels, Johannes; Seefried, Johannes; Ziegler, Marco; Mahr, Alexander; Urban, Nikolaus; Kühl, Alexander; Hüttel, Franziska; Franke, Jörg (8th International Electric Drives Production Conference (EDPC), 2018)

Elektromotorenproduktion 4.0: Potenziale des maschinellen Lernens in der Elektromotorenproduktion am Beispiel des Laserschweißens von Hairpins - Mayr, Andreas; Lutz, Benjamin; Weigelt, Michael; Gläßel, Tobias; Seefried, Johannes; Kißkalt, Dominik; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2019)

Erkenntnisse aus der Biegesimulation von Flachdraht - Weigelt, Michael; Fröschl, Christian; Masuch, Michael; Riedel, Andreas; Franke, Jörg (Draht, 2018)
<span style="background-color: transparent; color: rgb(102, 102, 102); font-family: Georgia, "Times New Roman", serif; font-size: 14px; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; line-height: 20px;">Dank einer simultanen Entwicklung aus struktur-mechanischer FE-Simulation und Versuchserkenntnissen lassen sich Formspulen von Traktionsmotoren kosten- und zeiteffizienter gestalten und innerhalb eines definierten Prozessfensters fertigen.

Evaluation of Machine Learning for Quality Monitoring of Laser Welding Using the Example of the Contacting of Hairpin Windings - Mayr, Andreas; Lutz, Benjamin; Weigelt, Michael; Gläßel, Tobias; Kißkalt, Dominik; Masuch, Michael; Riedel, Andreas; Franke, Jörg (8th International Electric Drives Production Conference (EDPC), 2018)

Explicit finite element analysis for rotary cutting of electrical steel sheet - Hubert, Markus; Weigelt, Michael; Spahr, Michael; Franke, Jörg; Hackert, Jürgen; Mehlhorn, Marcus (6th International Annual Engineering Seminar, InAES 2016, 2017)
Rotary cutting of rotor and stator laminations complements the available methods in the processing of electrical steel sheet. Furthermore, with this process, a technological answer to the production of ever-Thinner laminations can be found in which high-speed stamping is reaching its technical limits. This paper explicates a finite element analysis for the rotary cutting process of electrical steel. First an overview of the cutting process and its peculiarities is given. Then the setup for the FEM simulation and its material model are explained. Finally followed by a discussion of simulation results with different parameters.
Keywords: electric steel processing; finite element analysis; rotary cutting

Finite‑element‑analysis of the mechanical behavior of high‑frequency litz wire in flat coil winding - Weigelt, Michael; Thoma, Cornelius; Zheng, Erdong; Franke, Jörg (Production Engineering, 2020)
Numerous applications of daily life use flat coils, e.g. in the automotive area, in solar technology and in modern kitchens. One common property that all these applications share, is a flat coil made of high-frequency (HF) litz wires. The coil layout and the properties of the HF litz wire influence the winding process and the efficiency of the application. As a result, the HF litz wire must meet the complex technical requirements of the winding process and of the preferred mechanical, electromagnetic and thermal properties of the HF litz wire itself. Therefore, a reasonable configuration and optimization of HF litz wire has been developed with the help of a finite-element-analysis (FEA). In this work, it is first shown that the mechanical behavior of HF litz wire under tensile and bending stress can be simulated. Since the computational effort for modelling an HF litz wire at the single conductor level is hardly manageable, a suitable modelling strategy is developed and applied using geometric analogous models (GAM). By using such a model, HF litz wires can be designed for the specific application and their behavior in a winding process can be predicted.
Keywords: High frequency litz wire; Flat coil winding process; Inductive power transfer system; Finite element analysis; LS-DYNA

Lean 4.0 - A conceptual conjunction of lean management and Industry 4.0 - Mayr, Andreas; Weigelt, Michael; Kühl, Alexander; Grimm, Sebastian; Erll, Alexander; Potzel, Markus; Franke, Jörg (Procedia CIRP, Volume 72, 2018)

Manufacturing influences on transmission efficiency and thermal integration of resonant circuit modules of inductive power transmission systems for electric vehicles - Weigelt, Michael; Jordan, Sophia; Manger, Johanna; Kneidl, Maximilian; Masuch, Michael; Kühl, Alexander; Franke, Jörg (2023 IEEE Wireless Power Technology Conference and Expo, WPTCE 2023 - Proceedings, 2023)
Electromobility is the backbone of modern emission-neutral transportation systems. Wireless energy transfer via induction is the associated complementary technology that significantly improves the user-friendliness of energy supply in various use cases such as static or dynamic wireless power transfer (WPT). The functionality of WPT for electric vehicles is extensively demonstrated, but no automatable manufacturing processes exist to produce them in large scale. Therefore, this paper describes the manufacturing process chain of coil modules of inductive power transfer (IPT) systems and presents quality criteria for these coil systems. Using structured design of experiment (DOE), the manufacturing influences on the quality of the coil modules are presented and quantified. In addition, embedding concepts of the ground assembly (GA) capacitor configuration are qualitatively evaluated.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Assembly; Automotive; E-Road; Inductive Power Transfer; IPT; Production Systems; Wireless Power Transfer (WPT)

Methodical Comparison of Alternative Powertrain Technologies for Long-Distance Mobility Using Germany as an Example - Weigelt, Michael; Mayr, Andreas; Kühl, Alexander; Franke, Jörg (WEVJ (World Electric Vehicle Journal), 2019)
The main barriers to the wide acceptance of electric vehicles, such as the limited driving range or the high acquisition costs, are to be countered by various technology alternatives for the powertrain of the future. Promising developments include improved battery technologies, fuel cell technologies or a constant power supply of the vehicle while driving, for example through dynamic inductive charging. In this context, a holistic technology comparison would contribute to a comprehensive and understandable information situation by making the heterogeneous technological concepts comparable with regard to different evaluation criteria. Therefore, this work describes the basic assumptions of the proposed holistic comparison of alternative powertrain technologies for long-distance mobility. Relevant framework conditions are structured and a procedure for the evaluation of infrastructure expenditures is shown. Building on this, a selection of key performance indicators is defined and explained. The proposed KPI framework is applied to a passenger car in the economic area Germany. The results show that by using electrified roadways, ecological as well as economic advantages against other alternative powertrain designs can be derived.<br

Potentials of an Explicit Finite Element Analysis of the Bending Processes for Coated Copper Wires - Weigelt, Michael; Riedel, Andreas; Masuch, Michael; Mahr, Alexander; Gläßel, Tobias; Franke, Jörg (2017 7th International Electric Drives Production Conference (E|DPC), 2017)
The advancing electrification in industry and everyday life requires powerful electric drives providing highest efficiency. The winding as the core of these drives is subject to continuous development. Furthermore, it is of decisive importance to accelerate sample production for prototype construction and small series production of electric drives to shorten the innovation cycles. Coated bar-wound winding elements are increasingly important for the application in electric drives. The process window for damage free bending processes of coated copper wires is yet not defined. Structural mechanical finite element (FE) modelling is therefore a powerful tool to reduce costly trial-and-error loops and shortening development cycles for those production techniques as it provides reliable quantitative results. The aim of this paper is to propose the basics for defining a process window for the bending of flat wires using experimental bending test setups and FE-simulation tool
Keywords: finite element method; bending; flat wire

Potentials of machine learning in electric drives production using the example of contacting processes and selective magnet assembly - Mayr, Andreas; Meyer, Alexander Wilhelm; Seefried, Johannes; Weigelt, Michael; Lutz, Benjamin; Sultani, Darius; Hampl, Marcel; Franke, Jörg (2017 7th International Electric Drives Production Conference (EDPC), 2017)
Machine learning (ML) is a key technology in data driven industries. In general, ML algorithms offer insight in complex processes by analyzing measured data without acquiring in-depth domain knowledge. In contrast to common physical simulations they do not require excessive computational time and are well suited for real time analysis. This study focuses on transferring the potential of ML to the production of electric drives. Three major issues are identified: the preprocessing of the data, dealing with small data sets and the selection of an appropriate machine learning algorithm. Depending on the specific application in production, different algorithms, for example support vector machines, neural networks, random forests or boosted algorithms come into consideration. The potential of ML in electric drives production is demonstrated using two concrete applications: In the case of contacting technologies, such as thermo and ultrasonic crimping, ML algorithms for predictive maintenance, quality management and process control are considered. The second use case covers the selective magnet assembly. Here, a ML-based concept is proposed that predicts the cogging torque by analyzing magnet properties, as well as process parameters.<br
Keywords: machine learning; electric drives; magnet assembly; contacting technologies

Production Concepts for Inductive Power Transfer Systems for Vehicles - Kühl, Alexander; Kneidl, Maximilian; Seefried, Johannes; Masuch, Michael; Weigelt, Michael; Franke, Jörg (Energies, 2022)
The option of wireless energy transmission in electric vehicles can become the main market driver for electric vehicles due to its distinct advantages, such as range, weight, or costs, over conventional conductive charging solutions. In addition to the great potential, which different research work and realized systems have already shown, there are new requirements for the associated production networks in the automotive industry which must be addressed at an early stage. Furthermore, no solutions currently exist for the industrial production of these components. This paper presents the main components for the feasibility of wireless power transmission in electric vehicles. In addition, the required value chains and processes for the new components of the inductive power transfer systems, and the final assembly for induction coils, which has been developed at the FAU, will be presented. These include the developing of a winding process on a 15-axis special machine, ultrasonic crimping of the litz wire ends, and vacuum potting.<br

Quo vehis, Electromobility? - Weigelt, Michael; Mayr, Andreas; Böhm, Ralf; Kühl, Alexander; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2018)
The spread of electromobility is still far behind the objectives and expectations of politics and society. Up to now, the relatively high vehicle costs, politically sanctioned energy prices, the limited vehicle ranges and the inconvenient charging process represent the major barriers. At the same time, several drivers exist, such as the superior efficiency, emission-free driving, conservation of fossil resources and the impressive driving enjoyment. This article summarizes the drivers and barriers of the electromobility from an ecological, economic and social perspective. Finally, the challenges for the technology development and the production technology are derive

Quo vehis, Elektromobilität? - Weigelt, Michael; Mayr, Andreas; Böhm, Ralf; Kühl, Alexander; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2018)
Die Verbreitung der Elektromobilität in Deutschland liegt nach wie vor hinter den Zielen und Erwartungen von Politik und Gesellschaft zurück. Bisherige Hemmnisse der Mobilitätswende sind vor allem die relativ hohen Anschaffungskosten von Elektroautos, die politisch sanktionierten Strompreise, die begrenzten Reichweiten sowie der noch wenig komfortable Ladevorgang. Dem stehen wiederum zahlreiche Treiber wie der überlegene Wirkungsgrad, das emissionsfreie Fahren, die Schonung fossiler Ressourcen sowie der beeindruckende Fahrspaß gegenüber. Der vorliegende Beitrag fasst die aktuellen Treiber und Hindernisse der Mobilitätswende aus ökologischer, ökonomischer und sozialer Perspektive zusammen und leitet daraus Herausforderungen an die Technologieentwicklung und Produktionstechnik a

Schlussbericht zu dem Teilvorhaben "Automatisierte Fertigungstechnologien zum Biegen, Montieren und Schalten von innovativen Formspulenwicklungen" im Verbundprojekt "PRO-E-Traktion" - Gläßel, Tobias; Masuch, Michael; Weigelt, Michael; Kühl, Alexander; Franke, Jörg (2020)
Schlussbericht zu dem Teilvorhaben "Automatisierte Fertigungstechnologien zum Biegen, Montieren und Schalten von innovativen Formspulenwicklungen" im Verbundprojekt "PRO-E-Traktion" ("Automatisierte und robuste Produktionssysteme für E-Traktionsantriebe") Gefördert durch das Bundesministerium für Wirtschaft und Technologie, begleitet durch DLR e. V. Projektträger Förderkennzeichen: 01MX15011F Die Formspulentechnologie gilt als Schlüssel zur Realisierung leistungsdichter elektrischer Traktionsantriebe. Darüber hinaus stellt sie eine Möglichkeit dar, die gegenwärtig schlecht kontrollierbaren Wickelverfahren durch stabilere Biege-, Montage- und Fügeprozesse zu ersetzen. Allerdings waren zum Zeitpunkt des Projektbeginns die benötigten Technologien weder identifiziert, noch entwickelt und qualifiziert. Hier setzt das vorliegende Projekt an, indem es technologische Alternativen für die durchzuführenden Prozessschritte identifiziert und priorisiert. Basierend darauf werden vollautomatisierte Prozessketten zur Herstellung von Statoren mit Hairpinwicklung in unterschiedlichen Stückzahlszenarien konzipiert und in Simulationen validiert. Um darüber hinaus Potentiale alternativer Arten offener Formspulenwicklungen bewerten und gegenüberstellen zu können wird eine Referenzmaschine auf diese übertragen und eine Bewertungssystematik entwickelt und angewandt, in deren Ergebnis die produkt- und fertigungsseitigen Potentiale von Hairpinwicklungen bestätigt werden. Die identifizierten Kernprozesse des Biegens, Montierens sowie der Kontaktierung werden grundlegend analysiert und auf dieser Grundlage die Industrialisierbarkeit der Prozesse abgeleitet. Für die Herstellung der Hairpins zeigt sich eine Kombination des Rotationszugbiegeverfahrens mit einem Gesenkbiegeverfahren als aussichtsreich. Zur Montage der Hairpins in den Stator werden unterschiedliche Konzepte ausgearbeitet und validiert, wobei die Wichtigkeit einer geeigneten Führung der Formspulen herausgearbeitet wurde. Es zeigt sich, dass der Kontaktierung eine wesentliche Rolle in der Prozesskette zukommt, wobei gezeigt wird, dass sich mit einer Kombination aus laserbasierten Isolationsabtrag und Laserstrahlschweißen ein geeigneter Kontaktierungsprozess ableiten lässt. Die erzielten Ergebnisse tragen zu einer Senkung der Hürde bei der vollautomatisierten Herstellung von Statoren mit Formspulen-wicklung bei, da sie die Technologieauswahl, Prozessentwicklung sowie Anlagenplanung maßgeblich vereinfachen Bar-wound windings are regarded to be a key technology to realize electric traction drives with a high power density. Additionally, they provide an opportunity to replace recent winding technologies, that are characterized by a poor controllability, with bending, assembling and joining processes featuring a better process stability. Nevertheless, at the beginning of this project the technologies necessary were neither identified nor developed and qualified. To deal with these issues, the present project identifies and assesses technological alternatives for the process steps necessary. On that basis fully automated production chains for the production of stators with hairpin windings for different production volumes are designed and validated in simulations. Beyond that, the reference winding of this project is conveyed on alternative kinds of bar-wound windings. To be able to compare the resulting concepts, a rating system for bar-wound windings is developed that confirms the potentials of hairpin windings. The key process steps of bending, assembling and contacting identified in this project are analyzed fundamentally and based on these results, industrialization capabilities are derived. For the production of the hairpins, a combination of rotary draw bending and die bending proves to be promising. Different concepts to assemble the hairpins to the lamination are developed and analyzed. It is determined, that a suitable guidance of the bar-wound coil is necessary in any case. The analysis of the contacting process showed, that this process plays an important role in the process chain. Combining a laser based process for the removal of the insulation with a laser welding process is a suitable possibility to realize a reproducible contacting process. The results achieved contribute to a reduction of obstacles for the implementation of a fully automated production of stators with bar-wound windings, as they facilitate the selection of suitable technologies, the development of processes necessary and the planning of production facilities.
Keywords: bar-wound windings; Bending; Biegen; electric mobility; Elektromobilität; Elektromotor; enamelled wire; FKZ: 01MX15011F; Formspulenwicklung; Hairpin; hairpin windings; Hairpinwicklung; INSULATION; Isolation; Lackdraht; Laserschweißen; production technologies; Produktionstechnologien; Pro-E-Traktion; Stator; traction drives; Traktionsantriebe

Sustainability Aspects of Current Market Developments, Different Product Types and Innovative Manufacturing Processes of Electric Motors - Mayr, Andreas; Weigelt, Michael; Masuch, Michael; Adrion, Martin; Bauer, Aljoscha; Wirsinger, Katrin; Franke, Jörg (Applied Mechanics and Materials, Vol. 882, 2018)

Technical, Economical and Ecological Potentials of Electrified Roads - Franke, Jörg; Weigelt, Michael; Kneidl, Maximilian; Masuch, Michael; Kühl, Alexander (Wiener Produktionstechnik Kongress 2022, 2022)

Techno-Economic Evaluation of Strategic Solutions to Extend the Range of Electric Vehicles - Weigelt, Michael; Mayr, Andreas; Masuch, Michael; Batz, Kilian; Franke, Jörg; Bican, Peter; Brem, Alexander; Russer, Johannes A.; Russer, Peter (8th International Electric Drives Production Conference (EDPC), 2018)

Techno-Economic Evaluation of Technological Alternatives to Extend the Range of Electric Vehicles - Weigelt, Michael; Mayr, Andreas; Kühl, Alexander; Batz, Kilian; Bican, Peter; Russer, Johannes A.; Russer, Peter; Franke, Jörg (5th Annual Conference on Electric Roads & Vehicles, 2018)

Vergleich alternativer Technologien zur Reichweitenverlängerung von Elektrofahrzeugen - Weigelt, Michael; Mayr, Andreas; Franke, Jörg (7th Conference on Future Automotive Technology (CoFAT), 2018)